Border issue: misperception between Indonesia and Malaysia - Irwansyah, , (2017)
Indonesia and Malaysia border has been disputed and led to misperception.By using Krauss and Morsella’s misperception concept, this study described that the border issue was occurred only online community member who never existed at the border area.Online community members constructed the discourse about border issue based on the agenda of mass media.While online community members and mass media lead discussion on sovereignty and nationalistic ideology, local border people concerned how they maintain the mutual relationship. The misperception which leads to conflict in online community forum showed the extent of civil conflict mediated by mass and new media.